Thermal and Electrical Conductivity of Unsaturated Polyester Resin Filled with Copper Filler Composites - Kemal Yaman; Özer Taga (International Journal of Polymer Science)
Thermal and electrical conductivity of unsaturated polyester resin with copper filler composite material are investigated both theoretically and experimentally. In the experiments, polyester matrix is combined with dendrite-shape copper to determine the effects of both filler size and content on thermal and electrical conductivity, respectively. It is observed that the increase in the concentration causes the thermal and electrical conductivity of composite mixture to grow up. It has also been observed that the both thermal and electrical conductivity increase with increasing filler particle size.